2010
DOI: 10.1111/j.1469-8749.2010.03661.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercising attention within the classroom

Abstract: AIM To investigate whether increased physical exercise during the school day influenced subsequent cognitive performance in the classroom.METHOD A randomized, crossover-design trial (two weeks in duration) was conducted in six mainstream primary schools (1224 children aged 8-11y). No data on sex was available. Children received a teacher-directed, classroom-based programme of physical exercise, delivered approximately 30 minutes after lunch for 15 minutes during one week and no exercise programme during the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(99 citation statements)
references
References 21 publications
4
91
2
2
Order By: Relevance
“…6. During school time play occurs during recess or, as known in the UK, playtime.. Recess provides a break from classroom time and promotes learning behaviours, problem-solving skills, and learning readiness 5,11,12 Recess also offers children the opportunity to engage in physical activity on a daily basis. 13 In the United Kingdom, recess is mandatory and can account for up to 25% of the school day.…”
Section: Introductionmentioning
confidence: 99%
“…6. During school time play occurs during recess or, as known in the UK, playtime.. Recess provides a break from classroom time and promotes learning behaviours, problem-solving skills, and learning readiness 5,11,12 Recess also offers children the opportunity to engage in physical activity on a daily basis. 13 In the United Kingdom, recess is mandatory and can account for up to 25% of the school day.…”
Section: Introductionmentioning
confidence: 99%
“…The intervention study by Hill et al 1 provides an important basis on which to consider further the idea not only of the beneficial effects of exercise on cognitive achievement, but also of how best to provide exercise opportunities to those children who need them most. While in the past we might have assumed that this applied to those who do not access physical exercise out of school, it is becoming increasingly clear that physical exercise, as well as motor development more generally, is closely related to physical and mental health, as well as to cognitive achievement.…”
mentioning
confidence: 99%
“…4 Motor development, and its impact on other areas of physical and mental health as well as cognitive achievement, is also a central area of focus for those working with children with neurodevelopmental disorders. Hill et al 1 mention attention deficit-hyperactivity disorder, and other pertinent disorders include developmental coordination disorder (sometimes referred to as dyspraxia) and autism spectrum disorder. Such children experience significant motor and ⁄ or attention difficulties with suggestions of varying cognitive profiles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers documented that physical activity has positive effects on students academic test scores (Donnelly & Lambourne, 2011;Erwin, Fedewa, & Ahn, 2013;Hill et al, 2010;Hill, Williams, Aucott, Thomson, & Mon-Williams, 2011;Kibbe et al, 2011;Maeda & Randall, 2003;Reed et al, 2010) and on task behaviors (Bartholomew & Jowers, 2011;Carlson et al, 2015;Kibbe et al, 2011;Mahar et al, 2006;Miramontez & Schwartz, 2016). In a meta-analysis of 44 studies, Sibley and Etnier (2003) found a significantly positive relationship (effect size 0.32, p<.05) between physical activity and cognitive abilities of children.…”
Section: Physical Activity and School Performancementioning
confidence: 99%